2022
DOI: 10.1155/2022/1531474
|View full text |Cite
|
Sign up to set email alerts
|

Immune Infiltrates of m5C RNA Methylation-Related LncRNAs in Uterine Corpus Endometrial Carcinoma

Abstract: Aberrant 5-methylcytidine (m5C) modification plays an essential role in the progression of different cancers. More and more researchers are focusing on developing a lncRNA-based risk model to assess the clinical prognosis of cancer patients. However, the impact of m5C-related lncRNAs on the prognosis of patients with uterine corpus endometrial carcinoma (UCEC), as well as the immune microenvironment of UCEC, remains unclear. Here, we comprehensively analyzed the predictive value of m5C-associated lncRNAs in UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…These mRNAs regulated cell cycle progression accompanied by immune cell infiltration, which might lead to UCEC progression ( Zhao et al, 2022 ). Likewise, the findings indicated that the constituents of hazard models relying on the lncRNAs associated with m5C, m7G, or m6A could function as significant intermediaries of the immune milieu and promising prognosis biomarkers with therapeutic response in UCEC ( Gu et al, 2022 ; Sun et al, 2022 ; Chen et al, 2023 ; Zhou et al, 2023 ). Wang et al outline new insights into CNVs/SNVs in m6A regulatory genes which were associated with a negative impact on patient survival of EC and ultimately found that three genes, IGF2BP3, KIAA1429, and IGF2BP1 , were effective predictors of EC outcomes ( Wang et al, 2020 ).…”
Section: Network Resourcesmentioning
confidence: 92%
“…These mRNAs regulated cell cycle progression accompanied by immune cell infiltration, which might lead to UCEC progression ( Zhao et al, 2022 ). Likewise, the findings indicated that the constituents of hazard models relying on the lncRNAs associated with m5C, m7G, or m6A could function as significant intermediaries of the immune milieu and promising prognosis biomarkers with therapeutic response in UCEC ( Gu et al, 2022 ; Sun et al, 2022 ; Chen et al, 2023 ; Zhou et al, 2023 ). Wang et al outline new insights into CNVs/SNVs in m6A regulatory genes which were associated with a negative impact on patient survival of EC and ultimately found that three genes, IGF2BP3, KIAA1429, and IGF2BP1 , were effective predictors of EC outcomes ( Wang et al, 2020 ).…”
Section: Network Resourcesmentioning
confidence: 92%
“…FOXC2-AS1 acts as an oncogenic lncRNA in an m5c-dependent manner by stabilizing FOXC2 mRNA, which may provide a new therapeutic target for GC [ 185 ]. m5C-related lncRNAs have been found to play important roles in regulating the tumor-immune microenvironment in uterine corpus endometrial carcinoma (UCEC) and BLCA [ 85 , 186 ]. Figures 3 and 5 also summarizes the role of m5C modification in the regulation of tumor-associated lncRNAs.…”
Section: Functions Of Lncrna-rna Modification In Different Types Of C...mentioning
confidence: 99%
“…In an animal experiment, deletion of the m 5 C methyltransferase Nsun5 resulted in suppression of ovarian function and embryonic development arrest in mice [144]. In several bioinformatics studies on ovarian and endometrial cancers, m 5 C-related genes were closely associated with tumour chemotherapy sensitivity and overall survival [145][146][147]. In addition, abnormal m 5 C modification may be involved in TRDMT1-mediated granulosa cell death, which in turn causes premature ovarian failure [148].…”
Section: Other Rna Modifications In Female Reproductive System Diseasesmentioning
confidence: 99%